Training and participatory research in health promotion courses: Reflections and contributions for knowledge and experiences - Andrade Nunes, Nilza Rogeria; Mendes, Rosilda; Santos, Anabele Pires; Bittar, Cléria Maria Lobo [UNESP]; Edmundo, Kátia Maria Braga; Wallerstein, Nina (Springer Nature, 2022)
This chapter addresses training in participatory research through methodologies supported by action-reflection-action, as a pedagogical strategy for training in health promotion in undergraduate and graduate courses. The objective is to describe and analyze the contributions and reflections of participants in a health promotion course, composed of professionals from different areas of expertise. The course, consisting of eight modules, was offered as face-to-face workshops, following the methodological steps of community-based participatory research (CBPR) and also incorporating Paulo Freire's popular education pedagogy. The themes that guided the work span the dimensions of power, individual and community empowerment, participatory community-based research, partnerships, indicators, and evaluation. Participants stated satisfaction with the course purposes and recognized the activities and dynamics as appropriate tools for the development of subjective and objective skills, for collaborating in critical debates and for proposing ideas and solutions to face the challenges they face in their own community projects. Converting the methodology to a virtual environment was validated in 2021 and facilitated good results within hybrid configurations with community representatives and social movements in the shared construction of health promotion knowledge and action.
Keywords: Community-based participatory research; Health education; Health promotion; Professional training